ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ISLAMIC SOCIAL REPORTING PERUSAHAAN - PERUSAHAAN YANG TERDAPAT PADA DAFTAR EFEK SYARIAH TAHUN 2009-2011 - Septi Widiawati; Surya Raharja (Diponegoro Journal of Accounting, 2012)
The study aims to analyze the factors that may influence the companies that performed among List of Sharia Securities (Daftar Efek Syariah - DES) for years 2009-2011 to provide Islamic social reporting disclosure. DES are collection of securities that are not contradict with Islamic principles and have been approved by Bapepam-LK. DES are guide for Islamic mutual fund to put their funds and for Muslim investor to invest in Islamic securities. The factors are company’s characteristic that consists of firm size, profitability, industry type and classification of banks. In accordance to ISR index was knew how great the role of the company in conducting islamic social disclosure. The annual reports as data which can be obtained in Indonesian Stock Exchange and hypothesis testing using multiple liniear regression. The result of study examined that all factors have a significant to ISR disclosure.